Pragmatic trial evaluating the effectiveness of a patient navigator to decrease emergency room utilisation in transition age youth with chronic conditions: the Transition Navigator Trial protocol - Kyleigh Schraeder; Andrew Mackie; Gina Dimitropoulos; Susan Samuel; Eddy Lang; Scott Klarenbach; Greg Guilcher; Daniele Pacaud; Jorge Pinzon; Gail Andrew; Lonnie Zwaigenbaum; Shannon Scott; et al. (BMJ Open, 2019)
Introduction Transition to adult care is a challenging and complex process for youth with special healthcare needs. We aim to compare effectiveness of a patient navigator service in reducing emergency room (ER) use among adolescents with chronic health conditions transitioning to adult care.Methods and analysis Pragmatic randomised controlled trial parallel group design comparing ER visit rates between patients with access to a personalised navigator intervention compared with usual care. Unit of randomisation is the patient. Treatment assignment will not be blinded. Embedded qualitative study to understand navigator’s role and cost analysis attributable to the intervention will be performed. Patients aged 16–21 years, followed within a chronic disease clinic, expected to be transferred to adult care within 12 months and residing in Alberta during study period will be recruited from three tertiary care paediatric hospitals. Sample size will be 300 in each arm. Navigator intervention over 24 months is designed to assist participants in four domains: transition preparation, health system brokering, socioeconomic determinants of health and self-management. Primary outcome is ER visit rate during observation period. Secondary outcomes are ambulatory and inpatient care utilisation measures, as well as Transition Readiness Assessment Questionnaire score, and Short-Form Health Survey 12 (SF-12) score at 6 and 18 months post-randomisation. Poisson regression will compare rates of ER/urgent care visits between navigator and control participants, using intention to treat principle. Cost analysis of the intervention will be conducted. Thematic analysis will be used to identify perceptions of stakeholders regarding the role of navigators.Ethics and dissemination Ethics approval was obtained from the University of Calgary Conjoint Health Research Ethics Board (REB #162561) and the University of Alberta Health Research Ethics Board (Pro00077325). Our team is composed of diverse stakeholders who are committed to improving transition of care who will assist with dissemination of results.Trial registration number NCT03342495.